Moving towards Improvement in SA Abortion Legislation (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
As the author writes, the international news media are reporting that the US State of South Dakota legislature on March 1 (2006) has passed a Bill prohibiting abortions except where the mother’s life is endangered (the Senate by 23 votes to 12, following approval in the House of Representatives). The Governor has said he will sign the Bill into law.